Comparison of basin-scale in situ and meteoric 10Be erosion and denudation rates in felsic lithologies across an elevation gradient at the George River, northeast Tasmania, Australia - L. A. VanLandingham; E. W. Portenga; E. C. Lefroy; A. H. Schmidt; P. R. Bierman; A. J. Hidy (Geochronology, 2022)
Long-term erosion rates in Tasmania, at the southern end of Australia's Great Dividing Range, are poorly known; yet, this knowledge is critical for making informed land-use decisions and improving the ecological health of coastal ecosystems. Here, we present quantitative, geologically relevant estimates of erosion rates for the George River basin, in northeast Tasmania, based on in situ-produced 10Be (10Bei) measured from stream sand at two trunk channel sites and seven tributaries (mean: 24.1±1.4 Mg<mspace linebreak="nobreak" width="0.125em"/>km-2<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="e6bd9f1982fb337ba4d0bf6e2cf823c1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-4-153-2022-ie00001.svg" width="64pt" height="15pt" src="gchron-4-153-2022-ie00001.png"/></svg:svg>; 1σ). These new 10Bei-based erosion rates are strongly related to elevation, which appears to control mean annual precipitation and temperature, suggesting that elevation-dependent surface processes influence rates of erosion in northeast Tasmania. Erosion rates are not correlated with slope in contrast to erosion rates along the mainland portions of Australia's Great Dividing Range. We also extracted and measured meteoric 10Be (10Bem) from grain coatings of sand-sized stream sediment at each site, which we normalize to measured concentrations of reactive 9Be and use to estimate 10Bem-based denudation rates for the George River. 10Bem/9Bereac<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="387ba0141a914539abecece6249ac28e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-4-153-2022-ie00002.svg" width="72pt" height="16pt" src="gchron-4-153-2022-ie00002.png"/></svg:svg> denudation rates replicate 10Bei erosion rates within a factor of 3 but are highly sensitive to the value of 9Be that is found in bedrock (9Beparent), which was unmeasured in this study. 10Bem/9Bereac<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="d5b04f3154bc4bfebedc21679e942ad7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-4-153-2022-ie00003.svg" width="72pt" height="16pt" src="gchron-4-153-2022-ie00003.png"/></svg:svg> denudation rates seem sensitive to recent mining, forestry, and agricultural land use, all of which resulted in widespread topsoil disturbance. Our findings suggest that 10Bem/9Bereac<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="36f88919efe6ce2fa1edb5949cc0d3c5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-4-153-2022-ie00004.svg" width="72pt" height="16pt" src="gchron-4-153-2022-ie00004.png"/></svg:svg> denudation metrics will be most useful in drainage basins that are geologically homogeneous, where recent disturbances to topsoil profiles are minimal, and where 9Beparent is well constrained.